Contamination of hepatotoxic pyrrolizidine alkaloids in retail honey in China. (March 2018) - Zhu, Lin; Wang, Zhangting; Wong, Lailai; He, Yisheng; Zhao, Zhongzhen; Ye, Yang; Fu, Peter P.; Lin, Ge
Abstract: Pyrrolizidine alkaloids (PAs) are natural toxins present in over 6000 plants. Humans are exposed to PAs through the intake of PA-containing plants and/or PA-contaminated foodstuffs, such as honey. PA contamination in honey has been extensively studied in many countries, but rarely investigated in China. The present study investigated PA contamination in retail honey purchased in four representative regions (Hong Kong, Macau, Beijing, Shanghai) in China. Among 120 honey samples tested, 58% of them contained PAs with the concentration range over 0.04–288.07 μg/kg. The prevalence and content of PAs in honeys purchased in Hong Kong and Macau were significantly higher than those detected in Beijing and Shanghai. Lycopsamine and echimidine were determined as predominant PAs in the contaminated honeys, and their potential botanic sources including plants of Echium and Senecio genera were identified by pollen analysis. Moreover, clivorine, which has not been reported previously in PA-contaminated honey, was found with a high prevalence (34%) in PA-contaminated honeys in China. Our study represented an integrated report on PA contamination in retail honey in China. The data provided information useful for the global assessment of human risk posed by consumption of PA-contaminated honey. Highlights: The first study reporting the prevalence of PA contamination in honey in China. Evidence of botanical source of PAs in honey is found via pollen analysis. Clivorine is found for the first time as a predominant PA in honey in China.